Audyt wewnętrzny i controlling. Podobieństwa i różnice - Martyniuk, Olga (Internal Auditing and Controlling. Similarities and Differences, 2005)
The goal of the essay is to answer the question - Is it necessary to implement an internal auditing in a company, if there exists a controlling department? In order to answer that question, the author presents the similarities and differences between the internal auditing and controlling in the following aspects: the definition, the law regulations, tasks and requirements, place in a organization structure, the frequency of control, tools and methods, the effects of their activities.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 295-304